Toward a common understanding of diet-exercise strategies to manipulate fuel availability for training and competition preparation in endurance sport - Burke, L. M.; Hawley, J. A.; Jeukendrup, J.; Morton, J. P.; Stellingwerff, T.; Maughan, R. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
From the breakthrough studies of dietary carbohydrate and exercise capacity in the 1960s through to the more recent studies of cellular signaling and the adaptive response to exercise in muscle, it has become apparent that manipulations of dietary fat and carbohydrate within training phases, or in the immediate preparation for competition, can profoundly alter the availability and utilization of these major fuels and, subsequently, the performance of endurance sport (events >30min up to 24 hr). A variety of terms have emerged to describe new or nuanced versions of such exercise-diet strategies (e.g., train low, train high, lowcarbohydrate high-fat diet, periodized carbohydrate diet). However, the nonuniform meanings of these terms have caused confusion andmiscommunication, both in the popular press and among the scientific community. Sports scientists will continue to hold different views on optimal protocols of fuel support for training and competition in different endurance events. However, to promote collaboration and shared discussions, a commonly accepted and consistent terminology will help to strengthen hypotheses and experimental/experiential data around various strategies. We propose a series of definitions and explanations as a starting point for a more unified dialogue around acute and chronic manipulations of fat and carbohydrate in the athlete´s diet, noting philosophies of approaches rather than a single/definitive macronutrient prescription. We also summarize some of the key questions that need to be tackled to help produce greater insight into this exciting area of sports nutrition research and practice. Abstract from author